The critical role of EBUS‐TBNA cytology in the staging of mediastinal lymph nodes in lung cancer patients: A correlation study with positron emission tomography findings. Issue 9 (13th June 2017) - Lilo, Mohammed T.; Allison, Derek B.; Younes, Bouchra K.; Cui, Min; Askin, Fred B.; Gabrielson, Edward; Li, Qing Kay
Abstract : BACKGROUND: The sensitivity and specificity of positron emission tomography (PET) have been significantly improved for the identification of malignancies in recent years; however, it is still necessary to confirm PET findings in a lymph node (LN) by direct tissue sampling. Endobronchial ultrasound–guided transbronchial needle aspiration (EBUS‐TBNA) is the most commonly used approach for diagnosing and staging mediastinal LNs, particularly in lung cancer patients with locally advanced disease. Despite this fact, evidence‐based studies of EBUS‐TBNA cytology and PET findings are still suboptimal. METHODS: The electronic database at the Johns Hopkins Medical Institutions and the pathology archives were searched to identify patients with mediastinal lymphadenopathy who had both EBUS‐TBNA mediastinal LN sampling and a PET scan over a 14‐month period. Patients suspected of having lung cancer and patients with a history of lung cancer were included in this study. Cytological diagnoses and follow‐up surgical LN diagnoses were reviewed and correlated with PET scan findings. RESULTS: A total of 140 LNs from 79 patients, including 86 PET‐positive LNs and 54 PET‐negative LNs, were included. The most frequently sampled LNs were 4R and 7. The average size of PET‐positive and PET‐negative LNs was 1.2 and 1.6 cm, respectively. Among PET‐positive LNs, 41.9% were malignant, 41.9% showed reactive changes or granulomatous inflammation, and 9.3% were nondiagnostic by EBUS‐TBNA. However, among PET‐negative LNs, 74.1% showed reactive changes or granulomatous inflammation, 7.4% were malignant, and 18.5% were nondiagnostic by EBUS‐TBNA. CONCLUSIONS: The data demonstrate that EBUS‐TBNA cytology improves the diagnostic accuracy of mediastinal LNs and clinical staging. Furthermore, EBUS‐TBNA may identify additional malignant LNs (7.4%), and this highlights the risk for false‐negative findings with PET scanning in isolation. Cancer Cytopathol 2017;125:717‐25. © 2017 American Cancer Society . Abstract : Endobronchial ultrasound–guided transbronchial needle aspiration cytology significantly improves the diagnostic accuracy of positron emission tomography–positive lymph nodes and improves clinical staging. Endobronchial ultrasound–guided transbronchial needle aspiration may pick up additional malignant lymph nodes that would be missed by positron emission tomography alone.